2020
DOI: 10.1021/acs.energyfuels.9b04454
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Slag–Crucible Interaction on Coal Ash Fusion Behavior at High Temperatures

Abstract: Traditional ash fusion behavior is described by four characterization temperatures determined by shape of variation ash cone, cylinder, or cubes. The results by thermomechanical analysis (TMA) describe the whole fusion process, which supports the better understanding of the ash fusion process. However, the interaction between slags and the crucible at high temperatures is the key factor on the accuracy of the TMA measurement. In this work, the influence of the interaction between slags and different crucible m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Mo crucibles can also react with coal ash slag. 9 Coal ash fusion behavior was studied in crucibles of several materials, including Al 2 O 3 and Mo (Li et al 10 ). It was concluded that Mo crucibles can react adversely with basic oxides such as Na 2 O, CaO, and Fe 2 O 3 in coal ashes.…”
Section: Introductionmentioning
confidence: 99%
“…Mo crucibles can also react with coal ash slag. 9 Coal ash fusion behavior was studied in crucibles of several materials, including Al 2 O 3 and Mo (Li et al 10 ). It was concluded that Mo crucibles can react adversely with basic oxides such as Na 2 O, CaO, and Fe 2 O 3 in coal ashes.…”
Section: Introductionmentioning
confidence: 99%
“…Corundum exhibits outstanding slag resistance in many types of materials. It is a relatively ideal material for the study of wettability and has potential for industrial applications 25–31 . Herein, the wettability of CaO‐ and Fe 2 O 3 ‐modulated coal ash on corundum substrates is investigated, and the morphology of the wetted slag is evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…It is a relatively ideal material for the study of wettability and has potential for industrial applications. [25][26][27][28][29][30][31] Herein, the wettability of CaO-and Fe 2 O 3 -modulated coal ash on corundum substrates is investigated, and the morphology of the wetted slag is evaluated. The effects of the CaO/Fe 2 O 3 ratio on the slag's internal structure and crystal composition are clarified along with the alterations in the wettability of the crystalline compounds and wettability during slag spreading with different CaO/Fe 2 O 3 ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 5 conducted systematic research on limestone attrition and product layer development during fluidized-bed sulfation. Li et al 6 studied the influence of the slag−crucible interaction on coal ash fusion behavior at high temperatures. Hui et al 7 reported their improved understanding of the formation of the plastic layer during heating of Australian coking coal blends using three-dimensional image analysis techniques.…”
mentioning
confidence: 99%